Developments in the management of bone metastases with interventional radiology - Arrigoni, Francesco; Bruno, Federico; Zugaro, Luigi; Natella, Raffaele; Cappabianca, Salvatore; Russo, Umberto; Papapietro, Vito Roberto; Splendiani, Alessandra; Di Cesare, Ernesto; Masciocchi, Carlo; Barile, Antonio (Acta Biomedica Atenei Parmensis, 2018)
Interventional radiology has known an exponential growth in the last years. Technological advances of the last decades, have made it possible to use new treatments on a larger scale, with safe and effective results. They could be considered as palliative treatments for painful lesions but also curative procedures, as single treatment or specially in combination with other techniques (surgery, radiation and oncology therapies, etc.).The main diffuse techniques are those of thermal ablation that destroy the target lesion through the heat; however there are also endovascular therapies that destroy the target tissue thanks to devascularization. Finally the is also the possibility to stabilize pathological fractures or impending fractures. In this paper all the most diffuse and effective techniques are reviewed and also a discussion of the main indications is done, with an analisys of the success and complications rates.